IMPLEMENTASI MODEL TEAMS GAMES TOURNAMENT (TGT) DALAM MEMOTIVASI SISWA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SD ISLAM Al ABROR SITUBONDO TAHUN 2024 - Lidyawati, Reky (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Learning Islamic religious education requires a learning model that is able to activate students so that students are inspired by their learning motivation and are interested in their curiosity in learning Islamic religious education. By using this qualitative approach, the researcher attempted to describe the phenomena of implementing Islamic religious education learning using the TGT learning model at the Al Abror Islamic Elementary School in Situbondo in a detailed, comprehensive and complex manner based on data obtained from valid informants and carried out in a natural setting. The results of the research that has been carried out show that Islamic religious education teachers have been successful in using the TGT learning model in motivating students in learning Islamic religious education.